Oxygen Isotopes in Authigenic Clay Minerals: Toward Building a Reliable Salinity Proxy - D. Gebregiorgis; D. M. Deocampo; F. J. Longstaffe; A. Simpson; G. M. Ashley; E. J. Beverly; J. S. Delaney; J. Cuadros (Geophysical Research Letters)
Abstract Most clay minerals in sedimentary environments have traditionally been considered to be of detrital origin, but under certain conditions, authigenic clay minerals can form at low temperature through the transformation of precursor clays or as direct precipitates from lake water. Such clay minerals can hold important information about the prevailing climatic conditions during the time of deposition. We present the first quantitative reconstruction of salinity in paleolake Olduvai based on the oxygen‐isotope composition of authigenic clay minerals. We provide a framework illustrating that the isotopic signature of authigenic lacustrine clay minerals is related to the isotopic composition of paleo‐waters, and hence to paleosalinity. This new paleosalinity proxy shows that the early Pleistocene East African monsoon was driven by combinations of precession and obliquity forcing and subsequent changes in tropical sea surface temperatures. Such quantitative lacustrine paleosalinity estimates provide a new direction of research for modeling ecosystem change based on an ecologically relevant parameter.